Evolution of agricultural machinery parts restoration industry in Russia - V. P. Lyalyakin (Сельскохозяйственные машины и технологии, 2024)
The paper shows the effectiveness of agricultural machinery parts restoration by reducing metal and fuel consumption as well as labor costs. (Research purpose) The paper analyzes the evolution of the machine part restoration system during the agricultural industrialization process in Russia, and explores the role of industrial science in developing methodologies for machine repairing and part restoration. (Materials and methods) Publications on the history of the parts restoration industry were thoroughly reviewed. Special attention was given to the decrees issued by Soviet government bodies, including the targeted comprehensive program of the State Committee of Science and Technology, the USSR State Planning Committee, and the State Committee for Agricultural Technology. These programs were aimed at establishing and expanding the production base for the repair and restoration of agricultural machinery parts. (Results and discussion) In the early stages of agricultural industrialization, equipment repairs primarily involved the use of new spare parts, while worn parts were typically discarded for remelting. A significant advancement in parts restoration was the introduction of repair sizes for crankshafts and cylinder liners. Since 1975, the cost of maintaining equipment has surged sharply due to the prices of new spare parts. The paper also presents an analysis of the efforts by the All-Union Scientific and Production Association «Remdetal» to develop flow-mechanized lines and equipment for restoring agricultural machinery parts. (Conclusions) The paper illustrates the significant growth in parts restoration volumes, rising from 68 million rubles in 1965 to 539 million rubles in 1988, as well as metal savings that increased from 136 thousand tons to 1,110 thousand tons over the same period. Additionally it highlights the role of the USSR Academy of Sciences, leading scientific institutes, and machine-building enterprises in executing the targeted program to increase the restoration volumes of agricultural machinery parts and components.